(3fHPI aj GdJLhjO aj HjGf eNGQL GdMQhas ((3CMeO QaYJ s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO aEf GdETJZGd HJdGhI GdbQBf ef CUM GdJLGQGJ , hGdeOGheI Ydi JdGhJg ef CUM GdeYGedGJ s
(3BNQgG (B:s
(3hGdZfI JNQL ef GdNjThe eKd ZfI GdZRGdI GdaGbOI hdOgG JNQL ef NTegG JMf dgG GdbdhH agPg eNGQL GdMQha hGdMeO ddg QH GdYGdejf JeJ s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdbQGAGJ hGdJLhjOs